FINANCIAL HEALTH ASSESSMENT OF PT. PLN (PERSERO) 2019-2022: TOWARDS FINANCIAL SUSTAINABILITY - Regita Vyonda; Sanda Patrisia Komalasari (Pusat P2M Politeknik Negeri Batam, 2025)
This research aims to measure the financial performance of PT. PLN (Persero) in 2019-2022 uses financial ratios in accordance with the regulations of the Ministry of State-owned enterprises (BUMN). The sample for this research is PT PLN (Persero) financial report for four years. The research method used is a case study with an analysis of liquidity, solvency, activity and profitability ratios. The analysis was carried out based on the Decree of the Minister of BUMN No. KEP-100/MBU/2002. The research results show that the liquidity ratio of PT. PLN (Persero) was 95.02%, 64.98%, 58.63% and 82.30%, respectively. The solvency ratio shows debt to assets of 41.37%, 40.85%, 39.15% and 39.48%. Profitability ratios show ROEs of 0.47%, 0.64%, 1.34% and 1.45%. Based on this analysis, PT. PLN (Persero) was categorized as